Integrating Virtual Laboratory through Designing Worksheets STEM-PBL to Improve Students' Problem-Solving Skills in Junior High School - Buhera*, Rusdiman; Ikhsan, Muhammad; Wilujeng, Insih; Rahmawati, Laifa; Nurohman, Sabar; Natadiwijaya, Ismail Fikri; Muhammad, Al Jalali; Herlina, Herlina (Universitas Syiah Kuala, 2025)
Problem-solving skills are crucial in the modern era, so they become essential in increasing power competitiveness and adaptability. Research This aims to develop a virtual laboratory-integrated STEM-PBL worksheet. This research employs the research and development methodology using a 4D model. The validators consist of 4 media experts, content experts, and two practitioners. The readability test used 10 students selected from class VII by purposive sampling based on academic ability. This research shows that the STEM-PBL worksheet integrated with the virtual laboratory can increase students' problem-solving skills. Validation results show that all worksheet aspects are categorized as high with Aiken's Index value between 0.83-1.00. The practicality test of the worksheet obtained very practical category with a range value of 90-95% in all Implementation aspects of the worksheet, shows improving students' problem-solving skills with an overall N-gain of 0.51 (medium category), where improvement occurred in the solution implementation indicator (N-gain 0.70) and the lowest in solution evaluation